Open Innovation and Business Model of Health Food Industry in Asia - Nathapornpan Piyaareekul Uttama (Journal of Open Innovation: Technology, Market and Complexity, 2021)
Health trends and digital technologies are of great significance for the health and wellness food market and its development in the future. This study examines whether health trends, digital technology, and market concentration influence health and wellness food consumption in the Asian market. Our analysis uses a panel dataset covering 14 Asian economies from the period 2006–2020 and a panel quantile regression technique with non-additive fixed effects. The results reveal that health trends and digital technology have positive and significant impacts on health and wellness food consumption, whereas the concentration of distribution channels has a negative and significant impact. These results also offer insights into each type of health and wellness food consumption, thereby contributing to the health and wellness food market development. Finally, this study suggests the health and wellness food business development through a consumer-driven open innovation strategy.